The Convergence Angle of Full-coverage Crown Preparations Made by Dental Students - H. Dorriz; S. Nokar; R. Baghai Naini; A. Madadi (Tehran University of Medical Sciences, 2008)
Objective: A clinically feasible convergence angle in full-coverage crown preparations, meeting the requirements for proper retention and resistance forms, has always been a matter of interest for laboratory and clinical researches. This study aims to evaluate the angle in teeth prepared by both under- and post-graduate students at Tehran University of Medical Sciences, Faculty of dentistry, Department of Prosthodontics. Materials and Methods: Samples consisted of 196 prepared teeth for full-coverage crown restoration by third year postgraduate and fifth year undergraduate students in the Department of Prosthodontics. Two images were obtained from each die by a scanner and both bucco-lingual and mesio-distal convergence angles were measured, by two different assessors, via Auto CAD 14 software. The data were analyzed using analysis of variance. Results: There were statistically significant differences between the teeth prepared by un-der- and post-graduate students in mesio-distal convergence angles of all maxillary teeth, except for canines. Significant differences were found between bucco-lingual convergence angles of the maxillary canines and molars. Conclusion: The recently recommended convergence angles are more clinically feasible compared to the classic 4 to 10 degrees that was previously suggested for all teeth. It also seems that clinical experience does not necessarily lead to a decrease in convergence an-gles during preparation.